Biblical Interpretations and/as Queer Temporalities A Response - Hidalgo, Jacqueline M. (2020)
This response discusses the conjunction of “queer,” “temporalities,” and “biblical interpretation.” I argue that these essays demonstrate, through their turn to queer temporalities, that attending to queer time means attending to people in time, to their social practices, to dynamics of power, to violence, to survival, to the lost pasts whose voices still call out to our own, and to the choices we make in reading. The response also turns to borderlands theories, especially the work of Gloria Anzaldúa, and decolonial feminist thought, particularly that of María Lugones, in order to ask questions about biblical studies that cross borders.
Keywords: Gloria Anzaldúa; Binaries; Borderlands; decolonial thought; Decolonization; Queer Theory